The Effect of Adding Purple Sweet Potato (Ipomoea batatas L) on the Organoleptic Quality of Mocaf Flour-Based Pukis Cake - Shodiqin, Muhammad Ali; Chusnah, Miftachul; Hartanti, Dyah Ayu Sri (AGARICUS: Advances Agriculture Science & Farming, 2025)
Pukis cake is a traditional snack that is generally made from wheat flour. To reduce dependence on imported flour, mocaf is used as an alternative, along with purple sweet potato (Ipomoea batatas L.) as a natural coloring agent that also increases nutritional value and visual appeal. This study aims to investigate the effect of adding purple sweet potato (Ipomoea batatas L.) on the organoleptic properties of mocaf-based pukis cake, including color, aroma, taste, and texture. The experimental design used was a Completely Randomized Design (CRD) with three treatments: A1 (50 ml purple sweet potato), A2 (100 ml), and A3 (150 ml) per 500 ml of dough, each repeated three times. Data were analyzed descriptively and statistically using ANOVA, followed by the Least Significant Difference (LSD) test at the 5% level. Results showed that treatment A2 (100 ml purple sweet potato) yielded the best results with color values of 5.30, aroma 5.40, taste 5.40, and texture 5.25. The addition of 100 ml of purple sweet potato resulted in an attractive purple color, distinctive aroma, natural sweet taste, and soft texture that was significantly preferred by the panelists (p<0.05).